Meroe, Sudan. Connecting Foodways. Ein neues Projekt zu Esstraditionen in Nordost-Afrika und ihren kulturellen Verflechtungen - Nowotnick, Ulrike; Matthews, Steven (e-Forschungsberichte des DAI, 2020)
Focusing on past culinary practices, the “Connecting Foodways” project explores cross-cultural connections and technological transmission between the Middle Nile Valley and central and eastern Africa during the early Iron Age (ca. 1000 BC – 1000 AD). It is one of twelve projects of the DFG Priority Program “Entangled Africa” (SPP 2143), which explores inner-African relations and thereby develops new perspectives for joint archaeological research in Africa.